Pemanfaatan Perpustakaan Kantor Arsip, Perpustakaan, dan Dokumentasi Kota Padang bagi Masyarakat - Dewi, Bunga Cintya; Desriyeni, Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2015)
Based on the results of the research, concluded matters as follows. First, people use the library at the Archives, Library and Documentation city of Padang to obtain additional information and knowledge easily and quickly, gain additional knowledge outside school hours, can be used as a place of recreation and agents of social change. Second, what are the constraints faced by the community in the use of the library at the Archives, Library and Documentation city of Padang, namely, the lack of promotion of the library to the public, facilities and infrastructure are less complete, less librarians who participated, and the collection is still incomplete. Third, efforts should be made use of the library by the library in the community, namely, the promotion of more optimal, facilities and infrastructure that must be completed, as well as the training of librarians and collection more complete. It is therefore recommended: (1) provision of library collections must pay attention to the collection which are much needed user, (2) the library should be to provide funds for the procurement of collection and promote the library through the mass media and electronic media so that the public know of the existence of the library, (3) librarians should serve visitors more active role in finding the required information.Keywords:Â  libraries and community